Predicting Concentrations of Ultrafine Particles and Volatile Organic Compounds Resulting from Desktop 3D Printer Operation and the Impact of Potential Control Strategies. (6th April 2017) - Azimi, Parham; Fazli, Torkan; Stephens, Brent
Summary: Recent studies have shown that potentially hazardous volatile organic compounds (VOCs) and ultrafine particles (UFPs) are emitted from many desktop three‐dimensional printer and filament combinations. We use recently published measurements of UFP and speciated VOC emission rates from a number of desktop 3D printers and filaments to predict the magnitudes of human exposures to airborne pollutants that would be expected in multiple locations within a typical small office environment. We also model the impacts of several control strategies for reducing occupational exposures. Results demonstrate that UFP and VOC concentrations within close or moderate proximity (i.e., within 3 and 3 to 18 meters, respectively) to some desktop 3D printer and filament combinations with the highest emissions can exceed recommended exposure levels (RELs) for some VOCs and typical indoor concentrations for both UFPs and VOCs. Concentrations of caprolactam within close proximity to a printer using some nylon‐based filaments are predicted to exceed both acute and chronic RELs set by the California Office of Environmental Health Hazard Assessment. UFP concentrations are predicted to reach as high as 80, 000 particles per cubic centimeter in close proximity to the highest emitting printer and filament combinations. The printer and filament combinations with the lowest UFP and VOC emission rates are not expected to yield concentrations at levels of concern. The most effective control strategies for reducing both UFP and VOC concentrations included installing a high‐flow spot ventilation system and operating the printer in a sealed enclosure with high‐efficiency gas and particle filtration.